Research of external signs, microscopy and chemical composition of juglans regia l. partitions - N. V. Chebyshev; L. O. Martemyanova; A. V. Streliaeva; D. I. Lezhava; R. M. Kuznetsov (Сеченовский вестник, 2018)
Objective: to study the microscopy, external signs of walnut partitions and the chemical composition of the alcohol extract from this type of raw material.Materials and methods. Microscopy was prepared by the pharmacopoeial method. The chemical composition of the alcohol extract was investigated by chromato-mass spectrometry.Results. In the course of the work, external signs of walnut partitions and the chemical composition of the alcohol extract were studied.Conclusions. The analysis of alcohol extraction from walnut partitions was carried out, the content of basic biologically active substances was revealed. The main anatomical and diagnostic signs of walnut partition walls were studied. The data obtained can be used to write a pharmacopoeial article on this type of raw material.